2016
DOI: 10.1063/1.4959154
|View full text |Cite
|
Sign up to set email alerts
|

Note: Novel diamond anvil cell for electrical measurements using boron-doped metallic diamond electrodes

Abstract: A novel diamond anvil cell suitable for electrical transport measurements under high pressure has been developed. A boron-doped metallic diamond film was deposited as an electrode on a nano-polycrystalline diamond anvil using a microwave plasma-assisted chemical vapor deposition technique combined with electron beam lithography. The maximum pressure that can be achieved by this assembly is above 30 GPa. We report electrical transport measurements of Pb up to 8 GPa. The boron-doped metallic diamond electrodes s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…The temperature dependence of the resistance in the range of 300 to 0.2 K at ambient pressure was measured by a four-probe method using an adiabatic demagnetization refrigerator option on a physical properties measurement system (Quantum Design). The high-pressure generation and the in-situ transport measurements were performed using a DAC with boron-doped diamond electrodes [27][28][29]. The anvil culet and gasket hole had diameters of 300 µm and 200 µm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature dependence of the resistance in the range of 300 to 0.2 K at ambient pressure was measured by a four-probe method using an adiabatic demagnetization refrigerator option on a physical properties measurement system (Quantum Design). The high-pressure generation and the in-situ transport measurements were performed using a DAC with boron-doped diamond electrodes [27][28][29]. The anvil culet and gasket hole had diameters of 300 µm and 200 µm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we report development device which combines an EDLT structure into a DAC (Hereafter, we call this device the EDLT-DAC) for this task. We found that our previously fabricated DAC 26,27 with the microscale boron-doped diamond electrodes and the insulating un-doped diamond is suitable as the base of pressure generator with electric field-effect function. As a first sample to apply the field-effect and pressure, we chose a bismuth (Bi) film since it is well known that there are extremely few electrons and holes in Bi compared to conventional metals [33][34][35] and therefore it is expected to exhibit prominent response upon the electric field, for verifying the characteristics of the fabricated EDLT-DAC.…”
mentioning
confidence: 95%
“…Such a theory-guided search is becoming a steady approach for the exploration of new superconducting phase. We also have discovered new pressureinduced superconductors by using our original DAC 26,27 coupled with a data-driven approach [28][29][30] .…”
mentioning
confidence: 99%
“…First, electrical measurement probes are required to observe the superconductivity of the sample under extreme conditions. Specialized DACs with boron-doped diamond (BDD) probes have been developed to function stably under high pressure due to their superior chemical and mechanical hardness [12][13][14].…”
mentioning
confidence: 99%
“…The fabrication of the BDD components was conducted via a combination of electron beam lithography and microwave plasma-assisted chemical vapor deposition (Fig. 1(b)), as previously described in the literature [12][13][14]. The fabrication approach is applicable to various kinds of the diamond anvils, such as a culet-type of single-crystalline anvils and nano-polycrystalline anvils [21].…”
mentioning
confidence: 99%